DISPARITAS BATAS USIA PERKAWINAN DALAM PERATURAN PERUNDANG-UNDANGAN DI INDONESIA DAN HUKUM ISLAM PERSPEKTIF TEORI MASHLAHAH AT THUFI - Nina Agus Hariati (Institut Agama Islam Hasanuddin Pare, 2024)
Many marriages are carried out when a person is not yet mature enough. Therefore, in Islamic law and Indonesian law, limiting the age of marriage is a provision that is ijtihad in nature. Apart from that, regulations related to the age limit for marriage continue to undergo changes, in the process of which there are disparities between these regulations. This research will discuss the age limit for marriage from the perspective of Islamic law and law in Indonesia. This type of research is literature/library research using a conceptual approach using the mashlahahnajmudin at Tufi theory. From this research, it was found that the marriage age limit for men and women is the same, namely 19 years. To determine the age of marriage, methodologically it is based on the mashlahah najmudi at tufi method so that it does not conflict with the text and there is no specific text that can be used as a reference for performing qiyas. The concept of mashlahah is used to resolve the problem of unclear marriage age limits. Maslahah explained that the benefits of a particular place can be used as an explanation for the age limit for marriage, even though there is no detailed explanation in the text of the Al-Qur'an. The benefit referred to is the age limit for marriage which has been stipulated in Islamic law.